2020
DOI: 10.1111/ced.14186
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis in hidradenitis suppurativa: a cross‐sectional study and review of the literature

Abstract: Summary Background Coexistence of hidradenitis suppurativa (HS) and amyloidosis has been anecdotally described, but the association between these conditions is yet to be firmly established. Aim To study the association between HS and amyloidosis using a large‐scale computerized database, and to perform a literature review to characterize all reported patients with coexistent HS and amyloidosis. Methods A cross‐sectional study was conducted comparing the prevalence of amyloidosis among patients with HS and age‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“… 2‐10 Recently, Kridin et al retrospectively investigated 4417 patients with HS and found that 7 patients had amyloidosis. However, no information has been given about the type of amyloidosis and which organ has amyloid accumulation 1 . In case reports, the period to diagnose amyloidosis after HS onset has been reported to vary between 3 and 51 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2‐10 Recently, Kridin et al retrospectively investigated 4417 patients with HS and found that 7 patients had amyloidosis. However, no information has been given about the type of amyloidosis and which organ has amyloid accumulation 1 . In case reports, the period to diagnose amyloidosis after HS onset has been reported to vary between 3 and 51 years.…”
Section: Discussionmentioning
confidence: 99%
“…HS has been related to various cutaneous and systemic complications, such as chronic pain, anemia, hypoproteinaemia, lymphedema, squamous cell carcinoma, and amyloid A (AA) amyloidosis. 1 AA amyloidosis occurs due to amyloid deposited in various organs which is an acute-phase protein produced as secondary to chronic inflammatory diseases and it is a rare complication of HS. Amyloid storage usually starts from the kidneys and can also involve the heart, joints and nerves in AA amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the recent article by Kridin et al 1 . in Clinical and Experimental Dermatology .…”
mentioning
confidence: 99%
“…We read with great interest the recent article by Kridin et al 1 in Clinical and Experimental Dermatology. In that cross-sectional study, seven cases of amyloidosis (0.2%) were reported from a predominantly Jewish sample of 4417 patients with hidradenitis suppurativa (HS).…”
mentioning
confidence: 99%